Politicisation of the UK Armenian Diaspora: To What Extent Did War Cause A Transformation in the Political Identity of Armenians in the UK From 1913-1920 - Boghosian, Vahe (տպ. Atlas)
Trade diasporas are generally seen as apolitical, with limited exceptions. This paper will study the unexplored dynamics of the process by which trade diasporas become political under the stimulus of war. In doing so the research reveals that politicization occurs via a conversion of the trade diaspora network toward a structured communal hierarchy, led by a communal elite, which allows a stronger contribution to a national patriotic cause.
Keywords: History; Armenian diaspora; England